Synthesizing the motion of the vocal folds using optical flow based techniques. (April 2017) - Andrade-Miranda, Gustavo; Henrich Bernardoni, Nathalie; Godino-Llorente, Juan I.
Abstract : Graphical abstract: Abstract : Highlights: OF-based playbacks allow to visualize glottal dynamics in HSV automatically. OF-based playbacks include information about the mucosal wave. OF-based playbacks and traditional playbacks present a great correlation in shape. Complementary information to the common spatio-temporal representations is obtained. Abstract: Different playbacks have been proposed to synthesize the dynamical information of the vocal folds. However most of them rely on the delineation of the glottal gap using segmentation techniques which is a complex task and usually requires a manual supervision. In order to solve this issue, three new playbacks based on the optical flow computation are presented. Two of them, called Optical Flow Glottovibrogram and Glottal Optical Flow Waveform, analyze the global dynamics; and the remaining one, called Optical Flow Kymogram, analyzes the local dynamics. The reliability of the proposed playbacks is evaluated by comparison with traditional representations, showing a great correlation in shape with the traditional playbacks, and allowing the identification of the most important instants of time, such as closed-states and maximal opening. In addition, they provide complementary information to the common spatio-temporal representations, although the new playbacks are lightly blurred.